PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA DENGAN PENEMPATAN KERJA SEBAGAI VARIABEL MODERASI - Nabila Ulfa Walmi; Hafiz Rahman; Yulihasri (Halu Oleo University, 2024)
This research aims to obtain empirical evidence regarding the influence of organizational culture and job satisfaction on ASN performance with job placement as a moderating variable. This research was conducted at RSUD dr. Sadikin Pariaman. The sampling technique is a sampling technique, namely Stratified Proportional Sampling. This technique uses the number of samples taken from each stratum against the number of elements in each stratum so that the total sample is 103 ASN consisting of the management, the medical, the paramedic, and the support department. The analysis method used is descriptive statistical analysis using SmartPLS 3.0. Based on the results of research testing, it shows that organizational culture has insignificant effect on performance; job satisfaction has a positive and significant effect on performance; job placement has a positive and significant effect on performance; organizational culture and job satisfaction has a positive and significant effect with job placement as a moderating variable. Based on the results, the R square value of 0.434 means 43.4% of the ASN performance at dr. RSUD. Sadikin is explained by the variables organizational culture, job satisfaction, and job placement. Meanwhile, the remaining 56.6% was influenced by other variables not explained in this research.